Aerobic Training Is Better Than Resistance Training on Cardiac Function and Autonomic Modulation in Female ob/ob Mice - Stoyell-Conti, Filipe Fernandes; Irigoyen, Maria-Claudia; Sartori, Michelle; Ribeiro, Amanda Aparecida; dos Santos, Fernando; Machi, Jacqueline Freire; Figueroa, Diego Mendrot Taboas; Rodrigues, Bruno; De Angelis, Kátia (Frontiers in Physiology, 2019)
Objective: This study evaluated the effects of aerobic, resistance and combined exercise training on cardiac function and autonomic modulation in female ob/ob mice. Methods: 4-week-old female wild type and obese (ob/ob) mice were divided into 5 groups (n=8): control (WT), obese (OB) obese+aerobic training (OBA), obese+resistance training (OBR) and obese+combined training (OBC). The exercise training was performed on treadmill and/or ladder at 40-60% maximum test during 8 weeks. Cardiac function was measured using echo machine. Heart rate variability (HRV) was evaluated in the time and frequency domain. Results: OB group presented higher body weight gain(~600%), glycemia (~44%) and glucose intolerance (~150%), reduction of cardiac vagal modulation, evidenced by a lower RMMSD (~56 %), total power and high frequency band, and a higher isovolumic relaxation time (IVRT) (~24%) in relation to the WT group. Aerobic and combined training led to a lower IVRT (OBA: ~14%; OBC: ~14%) and myocardial global index (OBA: ~37%; OBC: ~44%). The OBA group presented an increased in vagal indexes of HRV than the other ob/ob groups. A negative correlation was observed between the delta of aerobic exercise capacity and MPI (r=0.45; p=0.002) and exercise capacity and body weight gain (r=0.39; p=0.002). Conclusion: Only the obese females underwent to aerobic exercise training showed improvement in cardiac function and HRV. Moreover, the aerobic exercise capacity, as well as, a greater responsivity to aerobic exercise training are intimately associated with these improvements, reinforcing the importance of aerobic exercise training to this population.